The genome sequence of a 45,000-year-old modern human from western Siberia - Fu, Qiaomei (Nature, 2014)
We present a high-quality genome sequence of a ~45,000-year-old modern human male from Siberia. This individual derives from a population that lived prior to – or simultaneously with – the separation of the populations in western and eastern Eurasia and carries a similar amount of Neandertal ancestry as present-day Eurasians. However, the genomic segments of Neandertal ancestry are substantially longer than those observed in present-day individuals, indicating that Neandertal gene flow into the ancestors of this individual occurred 7,000–13,000 years before he lived. We estimate an autosomal mutation rate of 0.4–0.6×10(−9)/site/year and a Y chromosomal mutation rate of 0.7–0.9×10(−9)/site/year based on the additional substitutions that have occurred in present-day non-Africans compared to this genome, and a mitochondrial mutation rate of 1.8–3.2 × 10(−8)/site/year based on the age of the bone.